An Analysis of Imperative Sentences in “The Boss Baby 1” Movie Script - Islam, Bangun; Nazri, M. Adib; Surayya, Ayu; Wati, Laila (Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to analyze imperative sentences found in the script of the movie